THE DEVELOPMENT OF LEARNING AIDS BASED ON ETHNOMATHEMATICS WITH SCIENTIFIC APPROACH FOR LEARNING GEOMETRY AT TECHNOLOGY MAJOR OF VOCATIONAL SCHOOL - Maulida Yulianti; Marsigit . (Jurnal Pedagogi Matematika, 2016)
This research was aimed to describe the quality of learning aids such as lesson plan and worksheets developed based on ethnomathematics. The lesson used a scientific approach to learn on geometry for vocational class of technology. There were three aspect of quality investigated. These were validity, practicality and effectiveness.  The learning aids were developed for technology major of vocational school students and the subject of product testing were students of class X TL 3 and the mathematics teacher at SMK Negeri 3 Yogyakarta, Indonesia. This development of learning aids used ADDIE model that includes five steps: analysis, design, development, implementation, and evaluation. The assessment of validity of lesson plan and worksheet was done by expert lecturer of the media development, expert lecture of instructional design, and mathematics teacher. The assessment of practicality was done by mathematics teacher and student. The effectiveness of worksheet was seen from the learning outcomes and the effectiveness of lesson plan was observed during the learning process.  The result of this research showed that Candi Borobudur as an ethnomathematics object which was developed into lesson plan and worksheet had validity score 3,75 and  3,91 (both of the maximum value 5) respectively. Then, it was shown to be easily used (score  4,10 from maximum 5), and effective for learning 54.17 percent of students understanding  after learning worksheet, and 79,68 percent of developed lesson plan could be implemented.  Keywords: learning tools, ethnomathematics,  scientific approach, geometry